Ceftaroline as Salvage Monotherapy for Persistent MRSA Bacteremia. (December 2016) - Burnett, Yvonne J.; Echevarria, Kelly; Traugott, Kristi A.
Objective: To summarize published data regarding the use of ceftaroline as salvage monotherapy for persistent methicillin-resistant Staphylococcus aureus (MRSA) bacteremia.Data Sources: PubMed (January 1980-June 2016) was searched using combinations of the search terms methicillin-resistant Staphylococcus aureus, MRSA, bacteremia, ceftaroline, refractory, and persistent . Supplemental references were generated through review of identified literature citations.Study Selection and Data Extraction: Available English-language, full-text articles pertaining to the use of ceftaroline for persistent MRSA bacteremia (MRSAB) were included.Data Synthesis: The PubMed search yielded 23 articles for evaluation. There are no randomized controlled trials to date—only case series and reports. Four retrospective case series detailing the use of ceftaroline as monotherapy for persistent MRSAB were included. Most patients received at least 4 days of an appropriate anti-MRSA antimicrobial prior to ceftaroline and were able to clear bacteremia within 3 days. The most common rationales for ceftaroline use were progression of disease or nonresponse to current therapy. Higher off-label dosing of ceftaroline is often utilized to achieve optimal pharmacokinetic/pharmacodynamic parameters. Adverse events are not well described due to lack of follow-up; however, neutropenia has been associated with prolonged use.Conclusions: Treatment options for persistent MRSAB remain few and far between. Ceftaroline is an effective agent for the salvage treatment of MRSAB. Off-label doses up to 600 mg every 8 hours are often used to achieve optimal pharmacokinetic/pharmacodynamic parameters. Because of lack of follow-up in these reports, the incidence of adverse effects of prolonged use of ceftaroline is not well defined.